2007
DOI: 10.1073/pnas.0704523104
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of olfactory information in Drosophila

Abstract: Investigating how information propagates between layers in the olfactory system is an important step toward understanding the olfactory code. Each glomerular output projection neuron (PN) receives two sources of input: the olfactory receptor neurons (ORNs) of the same glomerulus and interneurons that innervate many glomeruli. We therefore asked how these inputs interact to produce PN output. We used receptor gene mutations to silence all of the ORNs innervating a specific glomerulus and recorded PN activity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 43 publications
(53 reference statements)
11
123
0
1
Order By: Relevance
“…Furthermore, because all measurements were performed on neuron populations, the polarity of individual neurons may be lost in our recordings. Therefore, single cell measurements with activity dependent proteins, ideally combined with single cell electrophysiology (Galizia and Kimmerle, 2004;Wilson et al, 2004;Root et al, 2007) would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because all measurements were performed on neuron populations, the polarity of individual neurons may be lost in our recordings. Therefore, single cell measurements with activity dependent proteins, ideally combined with single cell electrophysiology (Galizia and Kimmerle, 2004;Wilson et al, 2004;Root et al, 2007) would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Functional imaging and electrophysiological studies have provided useful insights into information processing in the antennal lobe and mushroom body (39)(40)(41)42). Although local interneurons modulate PNs activity, ORNs are the primary drivers of this activity (43). Thus, odor experience-based plasticity in ORN coding is likely to influence PN tuning and enables the animal to identify an odor and assess its concentration in different environmental contexts.…”
Section: Discussionmentioning
confidence: 99%
“…LNs in the antennal lobe have been suggested to play a role in the transformation of olfactory information, and thus the shaping of elaborate behavioral responses to odor cues, through synaptic interactions with the ORNs and PNs in the antennal lobe circuitry (13,14,(25)(26)(27)(28)(29). Immunocytochemistry with a well characterized antiserum has revealed that DTKs are expressed in certain LNs that form a dense supply of neuronal processes to the antennal lobe glomeruli (21).…”
Section: Distribution Of Dtk Peptide and Its Receptor Dtkr In The Olfmentioning
confidence: 99%